RESULTS OF THE STUDY THE FAUNA AND ECOLOGY OF GROUND BEETLES (COLEOPTERA, CARABIDAE) OF THE HOLLOW IRGANAYSKAYA IN DAGESTAN - B. N. Saipullaeva (Юг России: экология, развитие, 2014)
It was studied the species composition and habitat distribution of carabids in Irganaysky basin of Dagestan. It is considered the features of ecology and seasonal dynamics of the activity of single dominant species.